Kebersatuan Manusia dengan Yang Ilahi: Perbandingan Antara Konsep Religiusitas St. Teresa Avila dengan Candi Borobudur - Ngatun, Markus (Aditya Wacana Pusat Pengkajian Agama Dan Kebudayaan, 2020)
The focus of this article is to compare the religiosity of St. Teresa of Avila and Candi Borobudur in achieving unity with the divine. The purpose of this analysis is to understand the concept of religiosity that is stored in the Borobudur temple and in the reflections of Theresa of Avila. Through a comparative methodology, the writer tries to compare the thoughts of both sides to find out their similarities and differences. The findings then reveal that there are several differences between them. These differences include the concept of God and the symbols they use. Through the inner castle,Teresa of Avila teaches that pilgrimage in human life are directed to God. While the Borobudur Temple does not explain that humans in their existence on this pilgrimage are directed to achieve unity with God. The similarity of both sides presents that unity of the people and the divine is the peak of human pilgrimage.